Der Zauberberg - Mann, Thomas 1875-1955 (Frankfurt am Main Fischer, 1967)
The narrative opens in the decade before World War I. It introduces the protagonist, Hans Castorp, the only child of a Hamburg merchant family. Following the early death of his parents, Castorp has been brought up by his grandfather and, later, by a maternal uncle named James Tienappel. Castorp is in his early 20s, about to take up a shipbuilding career in Hamburg, his home town. Before beginning work, he undertakes a journey to visit his tubercular cousin, Joachim Ziemssen, who is seeking a cure in a sanatorium in Davos, high up in the Swiss Alps. In the opening chapter, Castorp leaves his familiar life and obligations, in what he later learns to call "the flatlands", to visit the rarefied mountain air and introspective small world of the sanatorium.Castorp's departure from the sanatorium is repeatedly delayed by his failing health. What at first appears to be a minor bronchial infection with slight fever is diagnosed by the sanatorium's chief doctor and director, Hofrat Behrens, as symptoms of tuberculosis. Castorp is persuaded by Behrens to stay until his health improves.During his extended stay, Castorp meets a variety of characters, who represent a microcosm of pre-war Europe. These include Lodovico Settembrini (an Italian humanist and encyclopedist, a student of Giosuè Carducci); Leo Naphta, a Jewish Jesuit who favors totalitarianism; Mynheer Peeperkorn, a dionysian Dutchman; and his romantic interest, Madame Clawdia Chauchat.Castorp eventually resides at the sanatorium for seven years. As the novel concludes, the war begins, and Castorp volunteers for the military. His possible demise upon the battlefield is portended.
Paul Thomas Mann (1875-1955) was a German novelist, short story writer, social critic, philanthropist, essayist, and the 1929 Nobel Prize in Literature laureate. His highly symbolic and ironic epic novels and novellas are noted for their insight into the psychology of the artist and the intellectual. 'Der Zauberberg' is widely considered to be one of the most influential works of twentieth-century German literature.
Originally published in 1924
Keywords: 20th Century (1901-2000); Novel; Psychology; Philosophy; Germany